Perilaku Komunikasi Organisasi dalam Sosialisasi Program Kerja di Desa Wonorejo Kecamatan Gondangrejo Kabupaten Karanganyar - Sari, A Anditha; Syaifullah, Jahid (JURNAL SIMBOLIKA: Research and Learning in Communication Study, 2019)
The main purpose in this research is the picture of organizational communication behavior that occurs in the implementation of work program socialization in Wonorejo village Gondangrejo districts karanganyar district.From the description of the authors draw the communication patterns formed in the organization's communication and the success of communication behavior that is applied to the satisfaction of the community and the sustainability of development. Organizational communication behavior is a case in this study.One of the behavior of organizational communication in the government appears in the implementation of socialization of work programs to the community.Research conducted in Wonorejo village Gondangrejo districts karanganyar district also to track the perceptions of the people in the village work program that has been planned,and and how the level and form of citizen participation in welcoming the development program.The subjects of research are village apparatus and community leaders in Wonorejo village Gondangrejo districts karanganyar district.Techniques of collecting data using interviews, observation, and documentation. The data used were analyzed using descriptive analysis, whereas the validity of the data was tested by triangulation model. In conclusion, organizational communication behavior refers to the communication function within the organization that there are four functions in organizational performance, namely informative function, regulative function, persuasive function, and integrative function.